Knowledge and attitudes of patients with diabetes mellitus in a primary health care system - Oliveira, Kelli Cristina Silva de; Zanetti, Maria Lúcia (Revista da Escola de Enfermagem da USP, 2011)
The objective of this study was to characterize patients with type 2 diabetes mellitus, according to sociodemographic and clinical variables, and to analyze scores of knowledge and attitudes regarding the disease. Participants were 79 users who received care in a primary health care service, in 2008. The Diabetes Mellitus Knowledge (DKN-A) and Attitude (ATT-19) questionnaires were used for data collection. The population was formed by adults and elderly adults, who were between 30 and 80 years old. Most were literate (96.3%); married (63.3%); female (63.3%) and classified as class-2 obesity. As to the knowledge about the disease, subjects obtained scores lower than 8, indicating unsatisfactory results on self-care. Scores obtained regarding attitudes show difficulties to cope with the disease. Results evidence the need to adopt a Diabetes Education Program at the studied unit.